2006
DOI: 10.1016/j.cub.2006.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Phagosome Extrusion and Host-Cell Survival after Cryptococcus neoformans Phagocytosis by Macrophages

Abstract: Cryptococcus neoformans (Cn) is an encapsulated yeast that is a facultative intracellular pathogen and a frequent cause of human disease. The interaction of Cn with alveolar macrophages is critical for containing the infection , but Cn can also replicate intracellularly and lyse macrophages . Cn has a unique intracellular pathogenic strategy that involves cytoplasmic accumulation of polysaccharide-containing vesicles and intracellular replication leading to the formation of spacious phagosomes in which multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
392
4
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 371 publications
(424 citation statements)
references
References 19 publications
25
392
4
3
Order By: Relevance
“…However, it could also reflect a mechanism developed by the immune system in which macrophages overloaded with yeast cells transfer part of the fungal burden to uninfected or less-infected macrophages. Some of these phenomena (macrophage fusion, yeast extrusion, and transfer between macrophages) have been described in other fungal pathogens (1,2,13,15,16), which suggests that these processes represent a universal strategy developed by the host cells to control the infection independently of the pathogen engulfed.…”
Section: Discussionmentioning
confidence: 95%
“…However, it could also reflect a mechanism developed by the immune system in which macrophages overloaded with yeast cells transfer part of the fungal burden to uninfected or less-infected macrophages. Some of these phenomena (macrophage fusion, yeast extrusion, and transfer between macrophages) have been described in other fungal pathogens (1,2,13,15,16), which suggests that these processes represent a universal strategy developed by the host cells to control the infection independently of the pathogen engulfed.…”
Section: Discussionmentioning
confidence: 95%
“…Peripheral macrophages have shown that opsonization by IgM and complement activation is important for efficient phagocytosis of cryptococci. 79 For example, increased survival of healthy mice and immunosuppressed mice infected with opsonized cryptococcal cells was observed compared to unopsonized yeast cells. 33,80,81 Within the brain, the capabilities of a monoclonal anti-capsular IgG enhance microglial cell phagocytosis of cryptococci.…”
Section: Opportunistic Fungal Infectionsmentioning
confidence: 99%
“…neoformans, by which fungal cells and macrophages remain alive even after the release of yeast cells (25,26): MDMs clearly burst when releasing C. glabrata cells. The process is therefore more comparable to cytolysis, an escape mechanism used by bacterial species such as Chlamydia or Leishmania spp.…”
Section: Escape From Macrophagesmentioning
confidence: 99%
“…Cr. neoformans can also escape macrophages via extrusion/expulsion (25,26). The formation of massive vacuoles by the fungus is followed by extrusion of the phagosomes and the release of the pathogen.…”
mentioning
confidence: 99%